2020
DOI: 10.3904/kjim.2020.069
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis with rectal non-steroidal anti-inflammatory drugs

Abstract: Acute pancreatitis is the most common and feared adverse event associated with performance of endoscopic retrograde cholangiopancreatography (ERCP). Unremitting effort has been made for over 40 years to minimize the frequency and severity of this complication. Recently, the use of rectal non-steroidal anti-inflammatory drugs (NSAIDs) have opened a new era for its prevention. This review focuses on the role of NSAIDs in pancreatitis, the pharmacokinetics of these agents, and summarizes the results of clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
0
7
0
7
Order By: Relevance
“… 18 , 19 , 20 Mok SRS et al randomized, double blinded, placebo-controlled trial showed reduced incidence of PEP in ringer lactate plus rectal indomethacin versus normal saline plus placebo. 21 In our study we have also included NSAIDs (diclofenac intramuscular) in all cases however, various studies support effectiveness of NSAIDs given only per rectal compared to other routes. But in our country rectal NSAIDS is not easily available so we don't practice giving prophylactic rectal NSAIDs for pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 , 20 Mok SRS et al randomized, double blinded, placebo-controlled trial showed reduced incidence of PEP in ringer lactate plus rectal indomethacin versus normal saline plus placebo. 21 In our study we have also included NSAIDs (diclofenac intramuscular) in all cases however, various studies support effectiveness of NSAIDs given only per rectal compared to other routes. But in our country rectal NSAIDS is not easily available so we don't practice giving prophylactic rectal NSAIDs for pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Outra teoria bem elaborada em estudos científicos com animais mostra que uma forma induzível de ciclooxigenase-2 (COX-2) tem sido implicada como um importante mediador pró-inflamatório. A COX-2 é regulada em resposta a uma variedade de estímulos pró-inflamatórios, incluindo (celecoxib) 42 .…”
Section: Análise Estatísticaunclassified
“…Existe, sim, dentro do território brasileiro capítulos de livros cujo foco é a endoscopia; opiniões de especialistas, entre eles a do Prof. Dr. Paulo A indometacina e o diclofenaco seguem uma farmacocinética linear. A concentração plasmática e a área sob a curva são proporcionais à dose administrada, onde a meia vida e a depuração plasmática e renal não dependem da dose 42 . Elas são, rapidamente, absorvidas pelo trato gastrointestinal, após administração oral; com biodisponibilidade de 90% a 100% e concentrações plasmáticas máximas em hora e meia após sua administração 42 .…”
Section: Análise Estatísticaunclassified
See 2 more Smart Citations